Dampak Akreditasi Terhadap Kualitas Pengelolaan Lembaga Kursus Dan Pelatihan - Muhammad Ali Latif (Seminar Nasional LP2M UNM, 2019)
The study aims to get a picture of the quality of the management of the course and training institutions after getting accredited status in South Sulawesi; identifying factors supporting accredited Course and training institutions; and identifying factors that hamper accredited institutions. Courses and training in improving their quality. This research includes evaluation research, using a quantitative descriptive approach. Based on the results of research and data analysis, it was concluded (1) there was an improvement in the quality of the management of the Course and Training institutions in the Province of South Sulawesi which had been accredited in 2017; (2) get support (a) motivation and enthusiasm of the manager; (b) increasing teaching staff; (c) increasing learning / training facilities and infrastructure; (d) increasing managerial potential; (e) increasing frequency of meetings in discussing issues and developing courses and training institutions; (f) financial support from the government;  (g) increasing cooperation / partnership institutions; and (h) increasing participants in learning/training activities. (3) there are obstacles from (a) lack of professional teaching staff as needed; (b) lack of learning/training facilities and infrastructure;        (c) lack of funding to support operational costs and teacher incentives; (d) there has been no productive effort (e) the delay in funding support from the government when needed to support the learning / training program; (f) the number of competitors in the same course; and (g) the difficulty of establishing partner/collaboration institutions.